Successful treatment of Neuroblastoma in an adolescent with intra-arterial embolization before surgery - Luca Pio, MD (Journal of Pediatric Surgery Case Reports, 2017)
Introduction: Neuroblastoma in the adolescent is characterized by indolent growth and poor outcome. Surgical resection of the tumor is an essential part of the multimodality treatment. Surgical complications depend on the presence of Image Defined Risk Factors (IDRFs). Methods: We present an adolescent with pelvic neuroblastoma and epidural compression. To facilitate tumor resection, the patient underwent preoperative selective embolization. Results: After selective embolization a subsequent complete resection etraspinal localisation was performed without complication with complete remission after 2 years. Conclusions: Preoperative embolization is a safe and feasible technique that can help pediatric surgical oncologist to reduce complications IDRFs-related.